SEGURANÇA, EFICÁCIA E USABILIDADE DA FITA DE SILICONE NA FIXAÇÃO DO CATETER VESICAL DE DEMORA EM PACIENTES CRÍTICOS: ENSAIO CLÍNICO RANDOMIZADO DUPLO CEGO - Fabiana Martins de Paula (2022)
Adhesives are considered an integral part of healthcare contracting as they are provided to the patient. The indwelling veical catheter (CVD is a critical device that requires continuous) as a safety measure The ideal tape for yours has never been applied. Although underestimated and understudied, adhesive-related skin injury (MARSI) is a potential problem, particularly in critically ill patients and the skin as well as the use of adhesives. Silicone Adhesive Tape is the newest medical adhesive available and has appreciable qualities to fragile skin at risk for MARSI. Thus, the objective was to use the silicone tape and the usability of the silicone tape for patients, the safety of CVD in patients. This is a randomized clinical trial, blind to the evaluator and patient. The study was carried out in the adult Intensive Care Unit (ICU) of a hospital in August 2020, in February 2021. The secondary outcome was the satisfaction of nursing professionals and field research with the tapes. Data collection was performed by surveying trained and calibrated fields. The training comprised theoretical-practical classes on MARSI and the research protocol. Data were analyzed using mean and standard deviation for numerical variables and frequencies for categorical variables. The groups were compared using the Chi-square (χ²) or Fisher and Student's exact tests or the Mann-Whitney test, when appropriate. A total of 132 patients participated in the study: 66 in the intervention group (silicone tape) and 66 in the control group (acrylate tape). This study was approved by the Research Ethics Committee and registered in the Brazilian Clinical Trials Registry Platform (ReBEC). The incidence of MARSI was 28%: 4.3 per 100 patients/day. In the bivariate analysis, use and duration of mechanical ventilation (MV), length of stay in the ICU, score on the Braden Scale and on the Glasgow Coma Scale, edema, neurological diseases and use of sedatives were influencing factors for MARSI (p<0 .05). By logistic regression, length of stay in the ICU was an independent risk factor for MARSI (Odds Ratio [OR]: 1.072; 95% confidence interval [CI]: 2.1-12.5; p=0.005) and Scale score a protective factor (OR: 0.711; 95% CI: 0.3-49.3; p=0.048), whose higher scores indicated lower risk. The main type for MARSI was mechanical (91.8%), characterized by: skin peeling (56.7%), skin breakdown (18.9%) and tension or blister injury (16.2%); followed by irritant contact dermatitis (21.6%). There was no statistically significant difference between the groups regarding the number of events, type and severity of MARSI(p>0.05). However, partial (p=0.003) and global (p<0.001) detachment of the tapes were more frequent in the Silicone group. It is concluded that MARSI associated with CVD fixation is a significant problem in the ICU and partially preventable through screening and prevention protocols. Silicone tape is more expensive, just as safe as acrylate tape for CVD fixation, but of lower effectiveness. Thus, silicone tape should not be routinely used for CVD fixation in the ICU. RBR-6d73tn